Pengembangan Media Komik Berbasis Kearifan Lokal Luwu pada Tema 5 Pahlawanku di Kelas IV MI (Lembaga Pengembangan Kinerja Dosen, 2022)
This study has the objectives of (1) analyzing the need for developing comic media based on Luwu's local wisdom; (2) knowing the design of comic media development based on Luwu's local wisdom; (3) determine thevalidity of the development of comic media based on local wisdom in Luwu on the theme 5 My Heroes in class IV Al-Ikhlas Tanete Lampe'e North Luwu. The type of research used in this research is Research and Development (R & D) which develops a product in the form of comic media based on local wisdom and uses the ADDIE development model. Data collection techniques using observation, student questionnaires, teacher interviews and tests as data collection techniques. Fourth grade students of MI Al-Ikhlas Tanete Lampe'e are the objects of this research. The validity of a product can be known by conducting product validation tests, validated by experts in their fields, namely the first to material experts obtained a percentage value of 87.5% or very valid, the second to linguists the percentage value is 90% or valid, third to design experts it is known that the percentage value obtained is 90% which means that it is included in the very valid category.